Adults remember their birth weight, an important anamnestic item for cardiovascular and renal disease risk stratification - Crivelli-Meyer, Alexandra; Giannini, Olivier; Bianchetti, Mario Giovanni; Simonetti, Giacomo Domenico (Frontiers in Cardiovascular Medicine, 2022)
To assess how many adults remember their own birth weight, an important anamnestic item for cardiovascular and renal disease risk stratification, we conducted an inquiry among all employees of public hospitals of Ente Ospedaliero Cantonale (EOC) in Ticino region (Southern Switzerland). The results show that the vast majority of adults remember their own birth weight. Hence, it is reasonable to include this information in the stratification of risk for cardiovascular and renal diseases.